Performance Evaluation of Enterprise Knowledge Management System Based On Balance ScoredCard and FCEM Method (Case Study: Ministry of Roads And Transportation) - Mohammad Mousakhani; faranak nadi (Journal of Information Technology Management)
Despite the fact that most of the organizations have understood the importance of knowledge management and they have tried to implement that by some projects through their organizations but unfortunately many of this projects have not had high performance. So, one of the concerns of organizations is the continuous evaluation of knowledge management system performance. In fact performance evaluation of enterprise knowledge management system is capable of analyzing current situation of the system in whole and improvement of the system by general view of the advantages and disadvantages. The main goal of this research is, first prioritizing metrics of knowledge management system in Iran‘s Ministry of Roads and Transportation by Analytic Hierarchy Process (AHP) and second evaluating of knowledge management system performance based on Balanced Scorecard (BSC) by using Fuzzy Comprehensive Evaluation Method (FCEM). Based on the results, level of knowledge management system performance system in Iran‘s Ministry of Roads and Transportation is medium and at the end some suggestions are rendered for improving this system.